Efektivitas Media Video Tutorial dalam Meningkatkan Keterampilan Menyetrika Pakaian Seragam Sekolah bagi Anak Disabilitas Intelektual Ringan - Maifajri, Resi; Rahmahtrisilvia, Rahmahtrisilvia (Lembaga Yasin AlSys, 2024)
This research aims to prove that video tutorial media is effective in improving school uniform ironing skills for children with mild intellectual disabilities. This research uses a quantitative approach using the Single Subject Research type with an A-B-A design. The subject of this research was 1 child with mild intellectual disabilities in Class VII SLB Muhammadiyah Pauh IX Padang . The child cannot yet iron school uniforms. Technique data collection used is test deed . Then the data is analyzed with visual analysis of the graphs used For assess the data in condition And between condition . On baseline conditions (A1) were obtained inclination stability on range stability 3 .75 , mean level 25, limit above 26.875, limit below 23.125 and percentage 100% stability . On condition intervention (B) is obtained range stability 12 .75 , mean level 73.33, limit above 79.705, limit below 66,955 and percentage stability 16.66%. Then on baseline condition (A2) range stability 13 .5 , mean level 87.75, limit above 94.25, limit below 80.75 and percentage stability 75%. Results from research that has been done obtained that the skill of ironing school uniforms increased after intervention with video tutorial media . From the results the show that Video tutorial media is effective in improving school uniform ironing skills.